CONCERTOS FOR TROMBONE AND ORCHESTRA BY LEVKO KOLODUB: CONCEPTUAL PRINCIPLES OF INTERPRETATION - Yarovyi, Yurii (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2025)
Relevance of the study. The concertos for trombone and orchestra by L. Kolodub hold a prominent place in the Ukrainian musical heritage. Their interpretation requires not only technical precision but also a conceptual rethinking that reflects the multidimensional artistic potential embedded in the composer’s intention. In the context of modern performing practice, there is a growing need for a thorough exploration of interpretative strategies that extend beyond traditional execution and address the deeper semantic layers of musical works. This study responds to this need by proposing a comprehensive conceptual foundation for interpreting these compositions. Main objective of the study. The main aim of the article is to determine and theoretically substantiate the conceptual principles of interpreting the trombone concertos by L. Kolodub. The study seeks to demonstrate how interpretative awareness of stylistic, dramaturgical, and expressive elements enhances the performer’s role as a mediator between the composer and the listener. The Methodology. The study is based on an interdisciplinary methodological framework, which includes hermeneutic analysis (according to M. Mymryk’s triadic model of «experience — expression — understanding»), genre-stylistic analysis (to assess Kolodub’s individual approach within the instrumental concerto genre), structural-functional analysis (to explore the architecture and thematic dynamics of the concertos), and organological and performance-based methods (focusing on the expressive and technical potential of the trombone as a solo instrument in the 20th– 21st centuries). The hermeneutic approach enabled the identification of hidden meanings within the musical text and their interpretation through performer-driven artistic decisions. Main Results and conclusions. The research demonstrates that the concertos by L. Kolodub for trombone and orchestra are rich in stylistic synthesis, combining classical-romantic forms with innovative timbral solutions and elements of Ukrainian folklore. In particular, the First Concerto emphasizes idiomatic writing for the trombone, dramaturgical clarity, and expressive lyricism, while the Second Concerto offers broader possibilities for interpretative individuality, especially through cadenzas and thematic contrasts. The concept of «hermeneutic cyclicality» is highlighted as a key to grasping the multiple semantic layers of Kolodub’s music. The performer is positioned not merely as an executor of the score, but as an active co-creator who must engage with the folk-rooted musical idiom, respond to dramaturgical tensions, and construct a communicative dialogue with the audience. The findings underline the significance of Kolodub’s concertos for the development of both Ukrainian trombone performance and the broader discourse of modern academic music. This study enriches the understanding of interpretative paradigms in wind repertoire and affirms the artistic value of Kolodub’s contributions within the national and international musicological context. It also underlines the necessity for a performer’s conceptual preparedness and emotional empathy, which are crucial for achieving a meaningful musical narrative. The proposed conceptual principles offer a valuable framework for performers, educators, and researchers engaging with postwar Ukrainian music. Future investigations may expand on the comparative analysis of Kolodub’s concertos for different wind instruments, examine their reception history, and explore pedagogical applications in performance education. The evolving role of folk idioms in contemporary compositions also presents a fruitful direction for interdisciplinary inquiry in musicology and cultural studies